Ecotoxicological effects of lead (Pb) on the familia Anatidae:A systematic review - Bocanegra Olavarria, Diego (2024)
Among wild aquatic birds, the family Anatidaeis considered a convenient indicator of lead (Pb)contamination due to its exposure to this metal incontaminated inland waters. The objective of thisstudy was to determine the toxic effects of Pb onspecies of the family Anatidae. These species havebeen exposed to the heavy metal through activitiessuch as hunting, generating the main cause ofexposure, the ingestion of Pb pellets, either directlyor through their diet, which this activity uses. Pb, inspecies of this family, tends to bioaccumulate mainlyin the liver, kidneys and bones. Likewise, the mainconsequences of contamination by this metal arethe alteration of the immune system, a decrease inthe probability of survival and damage to the centralnervous system.